Conflict and Complexity Countering Terrorism, Insurgency, Ethnic and Regional Violence - Fellman, Philip Vos (Springer, 2015)
This volume represents a considerable investment of time, energy, and effort (not to mention patience) on the part of the many authors involved, but above all by Yaneer Bar-Yam and Ali Minai, with whom I began discussing the project at the sixth inter national conference on complex systems in 2006. While it took us a bit of time to actually move the project to completion (approximately 7 years), that time has been used to create a volume that is quite literally the first and only work of its kind. There have been other books which contain pieces of the puzzle of approaching terrorism with the tools of complex adaptive systems research. However, nowhere has there been such a comprehensive volume in which authors from such a wide variety of disciplines (political science, economics, history, sociology, geography, psychology, mathematics, computer science, and physics, to name just the most prominent disciplines drawn upon here) bring their skills to bear on the problems of terrorism, insurgency, battlefield warfare, and ethnic and regional violence...